2018
DOI: 10.15294/jpp.v35i2.13947
|View full text |Cite
|
Sign up to set email alerts
|

The Implantation of Character Values Toward Students Through Congkak Game for Mathematics Instructional Media

Abstract: This research aims to investigate character values that can be applied on students through congkak game as it is used as a media of mathematics learning. This study used qualitative and quantitative combination or (exploratory mixed methods designs). The first phase of qualitative data was taken through in-depth interviews to 5 selected informants using purposive sampling technique. All data interviews were analyzed thematically using NVivo qualitative analysis tool 10. Then, the second phase of the data was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 2 publications
2
34
0
10
Order By: Relevance
“…Salah satunya melalui inovasi dalam media pembelajaran. Media pembelajaran menjadi salah satu penentu suksesnya proses pembelajaran (Agusti, Zafirah, Anwar, & Syafril, 2018). Rumitnya persiapan dan banyaknya waktu yang diperlukan dalam Muslihatun, A., dkk.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Salah satunya melalui inovasi dalam media pembelajaran. Media pembelajaran menjadi salah satu penentu suksesnya proses pembelajaran (Agusti, Zafirah, Anwar, & Syafril, 2018). Rumitnya persiapan dan banyaknya waktu yang diperlukan dalam Muslihatun, A., dkk.…”
Section: Pendahuluanunclassified
“…Apabila pemain terbukti curang maka pemain tersebut dihukum atau didiskualifikasi. Selain kejujuran, permainan congklak juga mampu mengembangkan ketekunan, penghargaan, dan kerja keras (Agusti et al, 2018).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Basically, teachers are demanded to be flexible and creative in deciding which strategies and tools are used to implement the character-based instructional materials. However, the ultimate idea is how the character values are transferred, understood, and implemented (Agusti, et al, 2018). Thus, through character-based instructional materials, those actions are used in integrating between English language learning and character values.…”
Section: Introductionmentioning
confidence: 99%
“…Even Lestari and Afifah's (2016) research found that there was a significant effect of self-efficacy on learning motivation. Selfefficacy is the belief that someone can achieve the desired results, such as mastering a new skill or achieving a goal (Wade & Tavris, 2007;Agusti et al 2018).…”
Section: Introductionmentioning
confidence: 99%